Selective Neuronal Mitochondrial Targeting in SARS-CoV-2 Infection Affects Cognitive Processes to Induce ‘Brain Fog’ and Results in Behavioral Changes that Favor Viral Survival - Stefano, George B. (Med Sci Monit, 2021)
Alterations in brain functioning, especially in regions associated with cognition, can result from infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and are predicted to result in various psychiatric diseases. Recent studies have shown that SARS-CoV-2 infection and coronavirus disease 2019 (COVID-19) can directly or indirectly affect the central nervous system (CNS). Therefore, diseases associated with sequelae of COVID-19, or ‘long COVID’, also include serious long-term mental and cognitive changes, including the condition recently termed ‘brain fog’. Hypoxia in the microenvironment of select brain areas may benefit the reproductive capacity of the virus. It is possible that in areas of cerebral hypoxia, neuronal cell energy metabolism may become compromised after integration of the viral genome, resulting in mitochondrial dysfunction. Because of their need for constant high metabolism, cerebral tissues require an immediate and constant supply of oxygen. In hypoxic conditions, neurons with the highest oxygen demand become dysfunctional. The resulting cognitive impairment benefits viral spread, as infected individuals exhibit behaviors that reduce protection against infection. The effects of compromised mitochondrial function may also be an evolutionary advantage for SARS-CoV-2 in terms of host interaction. A high viral load in patients with COVID-19 that involves the CNS results in the compromise of neurons with high-level energy metabolism. Therefore, we propose that selective neuronal mitochondrial targeting in SARS-CoV-2 infection affects cognitive processes to induce ‘brain fog’ and results in behavioral changes that favor viral propagation. Cognitive changes associated with COVID-19 will have increasing significance for patient diagnosis, prognosis, and long-term care.